The Forest : A Fable of America in the 1830s - Nemerov, Alexander (Book collections on Project MUSE., 2023)
"Set amid the glimmering lakes and disappearing forests of the United States in the 1830s, The Forest: A Fable of America in the 1830s imagines how individuals at the time experienced their lives. Part truth, part fiction, this book follows painters, poets, enslaved individuals, farmers, and artisans through various settings. Some, such as Nathaniel Hawthorne, Nat Turner, Thomas Cole, and Edgar Allan Poe, are well-known; others are not. All are creators of private and grand designs, and makers of the worlds they inhabited. The Forest unfolds in brief stories. Each is an episode revealing a lost world of intricate relations: human beings going their own ways or crossing paths, in a place that is known to history, or is remote and unknown. For Alex Nemerov, the forest is a description of American society, as he writes, "the dense and discontinuous woods of nation, the foliating thoughts of different people, each with their separate life to lead." Nemerov's art history is at its center an experiment in writing, in how to write differently about visual culture. The Forest examines the history of the United States on a human scale, displaying the patterns of life alongside examples of paintings, prints, photographs and objects"--